PENGARUH KEMITRAAN DAN KOMPENSASI TERHADAP KINERJA AGEN DAN SUB AGEN MITRA PENJUALAN PT. GARUDA INDONESIA (PERSERO), TBK DI SEMARANG - M. V. I. Ron Olivia Mega Christy; Nawazirul Lubis; Bulan Prabawani (Universitas Diponegoro, 2015)
Compensation and partnership have an influence in improving performance agent and sub agent. Therefore, two things need to be considered by the company in order to improve agent and sub agent’s performance partner of sales PT. Garuda Indonesia (Persero), Tbk at Semarang is one of the airline companies that have partnered with ticket sales agents as a long-term marketing strategy and has a policy of applying the target system for product sales agent Garuda Indonesia but still there are some agents that have not been able to realize a given target.This study used sampling technique a sensus sampling approach to the 108 agent and sub agent to the certain considerations or criteria. Data collection techniques in this study using interview techniques, and by means of questionnaires and giuding question. The data obtained were analyzed quantitatively and describtive analize qualitative. Instrument of data collection (questionnaires) previously tested tools such as test validity, reliability testing. While, data analytical conducted through tabel analysis, simple linear regression, multiple linear regression and hypothesis testing with the t-test and F testThe conclusion of this study is that there is a positive effect between partnership and compensation of the agent and sub agent’s performance partner of sales PT. Garuda Indonesia (Persero), Tbk Branch Office Semarang. Therefore can be avowed good partnership and higher compensation of the agent and sub agent’s performance will increase, and vice versa. Suggestions for increasing agent and sub agent’s performance for the company to increase its attention to partnership and compensation for agent that will ultimately improve the performance of PT. Garuda Indonesia (Persero), Tbk too.